2013
DOI: 10.1186/1471-5945-13-13
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal, mixed method study to look at the experiences and knowledge of non melanoma skin cancer from diagnosis to one year

Abstract: BackgroundSkin cancer is the most common type of cancer in humans and the incidence is increasing worldwide. Our objective was to understanding the needs, experiences and knowledge of individuals with Non Melanoma Skin Cancer (NMSC) from diagnosis up until one year.MethodsPatients with NMSC completed questionnaires at diagnosis, treatment, 8 weeks post treatment and 12 months post diagnosis. Body image, psychological morbidity and Quality of Life (QOL) were assessed at each time point, with the exception of QO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 31 publications
(32 reference statements)
1
20
0
1
Order By: Relevance
“…22e24 A qualitative study in the UK found no significant difference in knowledge from diagnosis of NMSC to 8 weeks post treatment. 22 A similar Italian study in treated Squamous Cell Carcinoma patients found skin cancer knowledge to be low. 24 Both of these groups carried out patient interviews which suggested that lack of awareness was a significant reason for delay in presentation for treatment.…”
Section: Discussionmentioning
confidence: 93%
“…22e24 A qualitative study in the UK found no significant difference in knowledge from diagnosis of NMSC to 8 weeks post treatment. 22 A similar Italian study in treated Squamous Cell Carcinoma patients found skin cancer knowledge to be low. 24 Both of these groups carried out patient interviews which suggested that lack of awareness was a significant reason for delay in presentation for treatment.…”
Section: Discussionmentioning
confidence: 93%
“…Only three studies included keratinocyte carcinoma . Two studies included melanoma that had relapsed, two studies included stage I–III melanoma and one study included stage III melanoma .…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were conducted in the U.K., [21][22][23][24][25][26][27][28][29] three in the U.S.A. [30][31][32] and two in Australia. [33][34][35] Only three studies included keratinocyte carcinoma.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations